2017
DOI: 10.1038/s41559-016-0055
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic pleiotropy and mutation accumulation influence human senescence and disease

Abstract: Senescence has long been a public health challenge as well as a fascinating evolutionary problem. There is neither a universally accepted theory for its ultimate causes, nor a consensus about what may be its impact on human health. Here we test the predictions of two evolutionary explanations of senescence-mutation accumulation and antagonistic pleiotropy-which postulate that genetic variants with harmful effects in old ages can be tolerated, or even favoured, by natural selection at early ages. Using data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 38 publications
2
66
0
Order By: Relevance
“…The antagonistic pleiotropy and mutation accumulation theories of ageing both involve mutations as the cause of senescence and are not mutually exclusive (e.g., Rodriguez et al. ). Recent studies did provide some support for the mutation accumulation (e.g., Durham et al.…”
Section: State‐of‐art Of Our Current Knowledge In Relation To the Ninmentioning
confidence: 99%
See 1 more Smart Citation
“…The antagonistic pleiotropy and mutation accumulation theories of ageing both involve mutations as the cause of senescence and are not mutually exclusive (e.g., Rodriguez et al. ). Recent studies did provide some support for the mutation accumulation (e.g., Durham et al.…”
Section: State‐of‐art Of Our Current Knowledge In Relation To the Ninmentioning
confidence: 99%
“…2014 on Drosophila and Rodriguez et al. on humans based on genome‐wide analyses, see Flatt and Schmidt and Arbuthnott et al. for a broader discussion) and the antagonistic pleiotropy (as reviewed below).…”
Section: State‐of‐art Of Our Current Knowledge In Relation To the Ninmentioning
confidence: 99%
“…The MA hypothesis predicts that burden of slightly deleterious germline substitutions will increase with age due to the declining force of negative selection 3 . Our approach differs from earlier attempts to test this hypothesis [6][7][8][9][10][11]13,14 in two respects. First, instead of relying on intra-species variation to estimate mutational load, we used inter-species divergence, which may be statistically more powerful as it involves a larger number of substitutions.…”
Section: Discussionmentioning
confidence: 98%
“…In an indirect test of the expectation for inbreeding depression, outbreeding was reported to reduce age-related increase in mortality in hermaphroditic snails 13 , again in line with MA. Finally, Rodríguez et al 14 studied >2,500 human genetic variants linked to 120 genetic diseases and reported that variants associated with late-onset disease segregate at higher frequencies than those associated with early-onset disease, a third prediction under MA 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Considering that, several evolutionary theories of aging have been proposed and demonstrated to some extent, e.g. mutation accumulation (MA) and antagonistic pleiotropy (AP) 50 , 51 . Theoretical and experimental models for MA further support inbreeding effects for late-onset diseases 52 , 53 .…”
Section: Discussionmentioning
confidence: 99%